A institucionalização de padrões tecnológicos pelo PRONAF : uma análise do processo de adoção técnica na gestão de propriedades agrícolas familiares de Maringá-PR - Teixeira, Maísa Gomide (2007)
The diffusion processes of technical and managerial practices and their institutionalization in small rural organizations, which leads to their modernization, is analyzed in this study. The impact of the National Program for Family Farming Assistance (PRONAF), a Brazilian State program interested directly with the transfer of financial resources to the poorest segment of family farming in Brazil, is investigated. The issue is about verifying in which ways the entity responsible for technical assistance, through coercive mechanisms (since the financial assistance was dependent on following modern farming practices stipulated by that entity), generates conditions for technical professionalization among small farm owners situated in Maringá city, Brazil. Therefore, the research was based on authors who discuss technology as a structuration process where people construct certain interpretative schemes along the repeated engagement with them. However, simultaneously, rules and resources become elected structuring their continued interaction with those technologies, therefore expressing the recursive effect on both users and technology. Following this perspective, the institutional theory references consider the symbolic and interpretative aspects of the relation between structural properties and people's agency when responding to coercion. For our study a documental and field research of qualitative nature was taken place intending to grasp: "In which ways PRONAF - by credit - impacted on the institutionalization of new technological patterns on those rural family properties during the period of 1997 and 2006?". The elements researched were separated in two main groups representing different situations of dependency with the program: one of those farmers who had been involved with the loans offered by the program at the first years (1997-2000) and had broken ties with it at some time, thus were not upon the coercive links of the technical assistance; and the other group represented by the farmers who contracted the financial assistance recently (from 2002 until 2006) and were yet using the resources, therefore, were still subject to the requirements of implementing the techniques. The data was collected from both groups through interviews supported by a guide list of questions. This made possible the investigation of the internalization of the patterns transmitted by the technical assistance with the comparison of the interpretative schemes from the groups. The findings showed proximity between the interpretative schemes of the farmers in the two groups. So, if the farmers that received financial support (and the coercive pressure to follow new technical practices) at the first stages of the program still value those practices and believe in their efficiency as the farmers that are still connected to the Program, we can conclude that PRONAF is achieving, through coercion, its objective of modernizing small farms and professionalizing their technical and managerial workers. Moreover, the results also suggest that the analysis of the coercive diffusion of institutional patterns should consider cultural and relational aspects of people's contexts of reference.